Nurturing Religious and Moral Values at Early Childhood Education - Hernik Farisia (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This study aims to describe the process of nurturing religious and moral values to children at early childhood education since the development of this aspect is urgent to establish the laying foundation of students’ character in the next future. This research is a qualitative descriptive study which uses participative observation, in-depth-interview, and documentation to conduct the data. Meanwhile, the data analyses techniques used Miles & Huberman concept. The findings showed that nurturing religious and moral values within children at Aisyiyah 13 Kindergarten have been cultivated through scientific-based learning and indirect learning through morning activities. In the process of scientific-based learning, the teachers integrated the latest curriculum, al-Islam curriculum, and Kemuhammadiyahan with such materials that are faithful, worship, and morals. Based on the students’ performance, it is known that almost students achieved very good growth related to spiritual attitude. The last part of the article identifies the factor that supports students in enhancing religious and moral values that is the curriculum framework that accommodates religious classroom environment design and the role of teachers and principals. Meanwhile, the inhibiting factors of internalizing religious and moral values to early childhood were teachers got difficulties in integrating the core material of Curriculum 2013, al-Islam, and specific content based on the school affiliated to such as Kemuhammadiyahan